2018
DOI: 10.18041/2390-0512/bioc..1.2242
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización epidemiológica y clínica de la cirrosis hepatica en un centro regional del caribe colombiano: clínica general del norte. Enero 2012 a marzo 2017

Abstract: La cirrosis hepática es una de las enfermedades con mayor prevalencia y mortalidad en la población mundial; cuyas etiologías más importantes son de tipo alcohólica, virus de la hepatitis B y C, y esteatosis hepática no alcohólica; la caracterización epidemiológica y clínica, es fundamental para conocer  la casuística actual del problema. Se presenta un estudio descriptivo trasversal retrospectivo, con el objetivo de caracterizar epidemiológicamente y clínicamente a los pacientes con diagnóstico de cirrosis hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
4
1
1
Order By: Relevance
“…Regarding the etiology of cirrhosis, a study conducted in the Caribbean region of Colombia found that hepatitis C infection was the main cause of the disease, followed by non-alcoholic fatty liver disease 4 , which contrasts with the results of our study where alcohol consumption was identified as the etiology in nearly half of all cases of cirrhosis and viral hepatitis in only 7.3%, highlighting the regional epidemiological differences within the same country. Although in our study cryptogenic etiology surpassed non-alcoholic fatty liver disease as the cause of cirrhosis, it is possible that this is due to underreporting and the absence of a complete study of various cardiovascular risk factors in patients.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Regarding the etiology of cirrhosis, a study conducted in the Caribbean region of Colombia found that hepatitis C infection was the main cause of the disease, followed by non-alcoholic fatty liver disease 4 , which contrasts with the results of our study where alcohol consumption was identified as the etiology in nearly half of all cases of cirrhosis and viral hepatitis in only 7.3%, highlighting the regional epidemiological differences within the same country. Although in our study cryptogenic etiology surpassed non-alcoholic fatty liver disease as the cause of cirrhosis, it is possible that this is due to underreporting and the absence of a complete study of various cardiovascular risk factors in patients.…”
Section: Discussioncontrasting
confidence: 99%
“…In Colombia, the epidemiological behavior of cirrhotic patients has been described through retrospective and prospective studies aimed at characterizing the population receiving care in hepatology and gastroenterology outpatient services, as well as hospitalization in general wards 2 , 4 , 11 , 12 , 18 . The relevance of this study lies in the fact that, after an extensive literature review and to our knowledge, it is the first and largest of its kind, both locally and in Latin America, to describe the presentation of acutely decompensated patients in the emergency department based on the reasons for consultation or chief complaints.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…La población de este estudio es congruente epidemiológicamente con otros estudios realizados en Colombia en pacientes con cirrosis (17)(18)(19)(20) . La principal necesidad de información identificada entre los pacientes con CH fue la relacionada con las descompensaciones y complicaciones de la enfermedad, seguida por la de progresión y pronóstico, tratamiento farmacológico específico y efectos secundarios, riesgo de cáncer de hígado y necesidad de trasplante hepático.…”
Section: Discussionunclassified